Biochemical composition of the fruits of water chestnut (Trapa bispinosa Roxb.) - Alfasane, Md Almujaddade; Khondker, Moniruzzaman; Rahman, MA Mahbubar (Dhaka University Journal of Biological Sciences, 2011)
Key words: Aquatic plant; Trapa bispinosa; Biochemical composition; Fruits. DOI: http://dx.doi.org/10.3329/dujbs.v20i1.8879 Dhaka Univ. J. Biol. Sci. 20(1): 95-98, 2011 (January)